A imprensa republicana: um estudo de caso - Gebara, Ademir (Anais do Museu Paulista: História e Cultura Material, 1982)
This paper is a revised edition of the master thesis I submitted 1975 to the Department of History of the University of São Paulo, having as adviser Prof. Dr. Carlos Guilherme Mota. Two chapters of the original thesis have already been published respectively in the Anais de Assis and in the Anais do Museu Paulista. The present version benefitted from discussions held at the Department of History of UNICAM, especially in the frame of the project “Capitalismo e Agricultura’’.